2018
DOI: 10.7150/thno.26981
|View full text |Cite
|
Sign up to set email alerts
|

Increased recruitment of endogenous stem cells and chondrogenic differentiation by a composite scaffold containing bone marrow homing peptide for cartilage regeneration

Abstract: Even small cartilage defects could finally degenerate to osteoarthritis if left untreated, owing to the poor self-healing ability of articular cartilage. Stem cell transplantation has been well implemented as a common approach in cartilage tissue engineering but has technical complexity and safety concerns. The stem cell homing-based technique emerged as an alternative promising therapy for cartilage repair to overcome traditional limitations. In this study, we constructed a composite hydrogel scaffold by comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 61 publications
(78 reference statements)
2
85
0
Order By: Relevance
“…In a recent study, MSC recruitment into subcutaneously implanted scaffolds was studied and after just 1 week, there was evidence of MSC‐like cells present within the scaffold. [ 51 ] When applied at an orthotopic site in combination with microfracture, we envisage chondrogenesis might be even more pronounced due to the higher proportion of MSCs present in bone marrow.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, MSC recruitment into subcutaneously implanted scaffolds was studied and after just 1 week, there was evidence of MSC‐like cells present within the scaffold. [ 51 ] When applied at an orthotopic site in combination with microfracture, we envisage chondrogenesis might be even more pronounced due to the higher proportion of MSCs present in bone marrow.…”
Section: Resultsmentioning
confidence: 99%
“…Our in vitro experiment indicated no obvious degradation could be observed in PBS at 37 °C for 14 days (data not shown). In vivo , the environment of SAP hydrogel is much more complex than that in vitro so that the hydrogel showed good degradation 70 . After the implantation of nerve conduits with SAP hydrogels, Schwann cell, endothelial cells and fibroblasts migrate fast into the conduits and secret various enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…MSC recruitment and accumulation at burn sites increased the restorative effect, and this is consistent with previous study findings. 56 The decreased expression of pro-inflammatory markers and increased expression of anti-inflammatory agents suggest that MSCs exhibit anti-inflammatory activity. Several studies have revealed that MSC-secreted paracrine nutrition factors, such as VEGF, promoted the neovascularization of injured tissues.…”
Section: Discussionmentioning
confidence: 99%